PENGARUH PDRB, INDEKS PEMBANGUNAN MANUSIA DAN PENGELUARAN PEMERINTAH TERHADAP KETIMPANGAN REGIONAL - Athallah, T. M. Pasya; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of the Gross Regional Domestic Product (GDRP), Human Development Index (HDI) and Government Expenditure especially the Special Allocation Fund (DAK) on Regional Disparity in North Sumatera Province. The research method used is panel data regression analysis. The data used is quantitative data, obtained through the Central Bureau of Statistics (BPS) and also the Directorate General of Fiscals Balance (DJPK). The periode of this study are from 2012 to 2021. The results show that the Gross Regional Domestic Product (GRDP) variable and the Special Allocation Fund (DAK) variable have a positive and significant influence on regional disparity, while the Human Development Index (HDI) variable has a negative and significant effect on regional disparity. Therefore, it is hoped that the results of this study can support the regional governments of North Sumatera Province in making policies to reduce disparity between regions by taking into account of the distribution of the Gross Regional Domestic Product (GRDP) for each region, increasing the Human Development Index (HDI) through supporting on facilities and infrastructure who reflected through the allocation of the Special Allocation Fund (DAK).